PATIENT-CENTERED APPROACH IN THE TREATMENT OF PSORIASIS VULGARIS: PRESENTATION OF CLINICAL CASE - Denitsa Grozdeva; Mina Ivelinova; Yoana Rosenova (Peytchinski Publishing, 2022)
Introduction: Psoriasis is a complex, chronically recurrent, multifactorial disease that affects the somatic health (musculoskeletal, nervous, endocrine, cardiovascular, digestive systems) as well as the psyche and social adaptation. The organism's individual characteristics and tolerance to the applied therapy impose the need for complex treatment in order to achieve long-term clinical remission and change in the quality of life. Aim: to monitor the effectiveness of the patient-centered approach in the complex treatment of patients with psoriasis vulgaris. Case report: A 40-year-old woman with a 20-year-old history of psoriasis vulgaris visited the University Center for Eastern Medicine (UCEM-MU-Varna) with complaints of extensive, itchy erythemo-squamous plaques covering the body, face, scalp and limbs. The patient's disease progresses in a chronically recurrent course without long-term remission. We applied combined physical therapy, including laser acupuncture, magnetic therapy and aromatherapy. Results: After a 10-day treatment, we reported a reduction in the number and size of the plaques, subjective complaints and an improved psycho-emotional tone. When monitoring the condition during the 3rd, 6th and 9th month of the treatment, the patient reported no activation of the plaques and no other subjective complaints. The complex treatment, including conventional and unconventional physical factors, ensured a long-term remission of the disease. Conclusion: The patient-centered approach in the treatment of psoriasis vulgaris increases the effectiveness of the applied complex treatment. The selection and combination of conventional and unconventional physical factors selected according to the patient's tolerance help to slow the progression and ensure long-term remission of the disease.